189 Long-term outcomes of early-onset myocardial infarction with non-obstructive coronary artery disease. (8th December 2021) - Magnani, Giulia; Bricoli, Serena; Ardissino, Maddalena; Maglietta, Giuseppe; Nelson, Adam; Tagliazzuccchi, Guidoantonio Malagoli; Disisto, Caterina; Celli, Patrizia; Ferrario, Maurizio; Canosi, Umberto; Cernetti, Carlo; Negri, Francesco; et al.
Abstract: Aims: Data regarding long-term prognosis of MINOCA are very limited and conflicting. Methods and results: The Italian Genetic Study on early-onset MI enrolled 2000 patients who had a first MI before they were 45. The median follow-up was 19.9 years, the equivalent of 39 535 person-years. The composite primary endpoint was cardiovascular (CV) death, non-fatal MI, and non-fatal stroke (MACE); the secondary endpoint was rehospitalization for coronary revascularization. MINOCA was experienced by 317 patients (15.9%). The risk of MACE was not significantly different between MINOCA patients and those with obstructive coronary artery disease (MICAD, 27.8% vs. 37.5%; adj. HR: 0.79, 95% CI: 0.57–1.09; P  = 0.15, Figure 1). There was no between-group difference in the rate of non-fatal MI (17.3% vs. 25.4%; adj. HR: 0.76, 95% CI: 0.52–1.13; P  = 0.18), non-fatal ischaemic stroke (9.5% vs. 3.7%; adj. HR: 1.79, 95% CI: 0.87–3.70; P  = 0.12), or all-cause mortality (14.1% vs. 20.7%; adj. HR: 0.73, 95% CI: 0.43–1.25; P  = 0.26), but the rates of CV death (6.2% vs. 8.4%; adj. HR: 0.26, 95% CI: 0.08–0.86; P  = 0.03) and coronary revascularization (6.7% vs. 27.7%; HR: 0.27, 95% CI: 0.15–0.47; P  < 0.001) were lower in the MINOCA group. Conclusions: MINOCA is frequent in early-onset MI patients and is not benign with a long-term risk of MACE and overall mortality not significantly different from that of the MICAD patients. 189 Figure 1 Composite primary endpoint of CV death, non-fatal MI, and non-fatal stroke